2004
DOI: 10.1002/lapl.200410156
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of Malassezia yeasts on human skin using confocal laser scanning microscopy

Abstract: Fiber-based confocal laser scanning microscopy affords a vast field of application in medical research and clinical practice. The application of fluorescent dye allows real-time imaging of yeasts of the genus Malassezia on human skin in vivo. An Ar + -laser is used to excite the fluorescent food dye sodium fluorescein at 488 nm. Its emission is simultaneously detected in the spectral region from 500-600 nm. Topically applied fluorescein labels fungal microstructures in native habitat. Cumulative intradermal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 13 publications
0
27
0
1
Order By: Relevance
“…This is most likely due to the fact that sebaceous glands exhibit lower activity and different sebum composition before puberty . Yeasts were also identified in the infundibulum by light and electron microscopy in biopsy samples and in vivo on the scalp by confocal laser scanning microscopy …”
Section: Composition Of the Microbiome On The Scalp Surface And In Tementioning
confidence: 99%
“…This is most likely due to the fact that sebaceous glands exhibit lower activity and different sebum composition before puberty . Yeasts were also identified in the infundibulum by light and electron microscopy in biopsy samples and in vivo on the scalp by confocal laser scanning microscopy …”
Section: Composition Of the Microbiome On The Scalp Surface And In Tementioning
confidence: 99%
“…The histopathological findings of lesional skin biopsy specimens in PV demonstrated that follicular abnormalities included atrophy, degeneration, miniaturization, keratotic plugs and infundibular dilatation, as well as a slight hyperkeratosis and mild acanthosis. Malassezia is known to reside within the infundibulum of the hair follicle, suggesting that PV is a hair follicular centric infectious disease. Consistent with this hypothesis, hair loss and/or thinning within PV lesions were reported .…”
Section: Pityriasis Versicolormentioning
confidence: 99%
“…CLSM can be applied both in vitro and in vivo. For example, Meyer et al imaged Malassezia yeasts on living human cutaneous tissue using sodium fluorescein to label both the skin surface and the micro-flora structures with this method (Meyer et al, 2005). As well as visualising the penetration of substances into the skin, the effect of encapsulation of a dye into particles on the penetration pathways can be studied (Ossadnik et al, 2006), and CLSM can be used to study morphological changes of the skin (Dietterle et al, 2008, Eichert et al, 2010, Meyer et al, 2007.…”
Section: A C Bmentioning
confidence: 99%